Vows of empire - Skrutskie, Emily, 1993- (Skrutskie, Emily, 1993- Bloodright trilogy, 2022)
Separated for the first time and in full command of their respective forces, the time has finally come for Gal and Ettian to confront what they owe their empires, their friends, and each other if they are ever to forge a universe where the two of them can be together.